1998
DOI: 10.1029/98jd01880
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes and global warming potentials for dimethyl ether and for fluorinated ethers: CH3OCF3 (E143a), CHF2OCHF2 (E134), CHF2OCF3 (E125)

Abstract: Abstract. Using recent kinetic data, two-dimensional (2-D) chemical-transport modeling of the atmospheric lifetimes of dimethyl ether and fluorinated ethers CH3OCF 3 (E143a), CHF2OCHF 2 (E134), and CHF2OCF3 (E125) shows that E134 and E125 have substantially larger lifetimes than previously estimated. Dimethyl ether has a short atmospheric lifetime of 5.1 days and a relatively insignificant radiative forcing leading to a relatively low global warming potential. Increasing fluorination is accompanied by slower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 20 publications
0
70
1
1
Order By: Relevance
“…Moreover, DME does not produce soot [6,8]. Apart from above merits, the global warming potential for DME has been modeled and the results indicate that DME has a global warming potential of 0.1 for a 500-year time horizon, which is much lower than diesel [9]. Another important aspect is that DME has the highest well-to-wheel efficiencies next to natural gas among all non-petroleum based fuels no matter what type of vehicle technologies are applied including conventional, hybrid, and fuel processor fuel cell [6].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, DME does not produce soot [6,8]. Apart from above merits, the global warming potential for DME has been modeled and the results indicate that DME has a global warming potential of 0.1 for a 500-year time horizon, which is much lower than diesel [9]. Another important aspect is that DME has the highest well-to-wheel efficiencies next to natural gas among all non-petroleum based fuels no matter what type of vehicle technologies are applied including conventional, hybrid, and fuel processor fuel cell [6].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, heat integration with the objective function of minimizing utility costs has been Fuel Processing Technology 131 (2015) [7][8][9][10][11][12][13] performed to optimize the heat exchange network (HEN). The production of DME via tri-reforming has two significant advantages: 1) CO 2 emission from flue gas of power plant is mitigated without extra CO 2 separation unit operations and 2) a viable carbon resource is converted into a useful chemical compound (DME).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is quite non-hazardous for being nonmutagenic, noncarcinogenic, nonteratogenic, and nontoxic. Wuebbles et al 28 reported that the global warming potential of DME is lower than that of carbon dioxide, methane, and dinitrogen oxide, demonstrating its ecofriendliness. However, it is flammable 29,30 and, thus, safety precautions must be followed when handling DME.…”
Section: -27mentioning
confidence: 99%
“…Computational studies have predicted the IR spectra of several fluorinated ethers and provided estimates of radiative forcings [7][8][9][10]. Information on lifetimes has come from several recent kinetics experiments [4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%